2001
DOI: 10.1016/s0736-0266(00)00044-9
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of fracture stability influences chondrogenesis, osteogenesis and immigration of macrophages

Abstract: Mechanical conditions at the fracture line determine the mode of fracture healing (osteonal versus non-osteonal bone union). The aim of this study was to investigate the influence of differing degrees of fracture stability on the time course of chondrogenesis, enchondral ossification and immigration of macrophages into the fracture callus.Using a fracture model of the rat's tibia, histological (Azan staining), immunohistological (antibodies directed against the macrophage-specific surface antigen ED2), and mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 27 publications
(18 reference statements)
0
40
0
3
Order By: Relevance
“…Circumstantial support for this hypothesis includes mRNA expression of macrophage macrosialin protein correlating with the expression of collagen IX in fractures. 30 In addition, colony stimulating factor-1 treatment over an extended time course (14 days) in rabbits resulted in a significantly increased mineralized callus area at 4 weeks post fracture, with no coincident increase in osteoclast or osteoblast number. 63 Macrophages were not assessed in this study, but given that they are a major colony stimulating factor-1 target it raises the possibility that either increased macrophage numbers or enhancement of a particular macrophage phenotype contributed to the observed increase in callus mineralization.…”
Section: Macrophage Participation In Hard Callus Formation and Remodementioning
confidence: 93%
See 2 more Smart Citations
“…Circumstantial support for this hypothesis includes mRNA expression of macrophage macrosialin protein correlating with the expression of collagen IX in fractures. 30 In addition, colony stimulating factor-1 treatment over an extended time course (14 days) in rabbits resulted in a significantly increased mineralized callus area at 4 weeks post fracture, with no coincident increase in osteoclast or osteoblast number. 63 Macrophages were not assessed in this study, but given that they are a major colony stimulating factor-1 target it raises the possibility that either increased macrophage numbers or enhancement of a particular macrophage phenotype contributed to the observed increase in callus mineralization.…”
Section: Macrophage Participation In Hard Callus Formation and Remodementioning
confidence: 93%
“…Data from animal models support the fact that macrophages are present within repair-associated tissues during this early anabolic phase with potentially sustained presence of robust numbers of macrophages during rigidly stabilized fixation compared with nonrigid repair scenarios. 12,29,30,50 During intramembranous ossification, macrophages were intercalated throughout areas of developing bone matrix, 12 whereas during endochondral repair they were excluded from the developing cartilage but were present in adjacent tissues. 29 Similarly, human fracture tissue studies support that, although macrophage numbers are higher in early fracture samples, they do persist in fractureassociated tissues and have been observed in association with Macrophages in bone repair AC Wu et al areas of bone formation.…”
Section: Macrophage Contributions To Early Anabolism During Fracture mentioning
confidence: 99%
See 1 more Smart Citation
“…HIV has also been shown to affect other chemical mediators, including interleukins 1 and 6 and tumour necrosis factor, which have been shown to play a role in the fracture repair process [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse model of tibia fracture, both resident macrophages and inflammatory circulating macrophages were shown to be vital for the deposition of collagen type I (126). Furthermore, it has been shown that the gene expression of macrophage macrosialin protein is positively associated with the expression of collagen in fractures (127). In summary, macrophages are active during whole repair phase working synergistically with MSCs to help forming of collagen matrix and formation of new blood vessels.…”
Section: Macrophagesmentioning
confidence: 96%